2019
DOI: 10.3390/cells8070655
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Novel Pyrazole Ethandiamide Compounds as Inhibitors of Human THP-1 Monocytic Cell Neurotoxicity

Abstract: Neuroinflammation and microglia-mediated neurotoxicity contribute to the pathogenesis of a broad range of neurodegenerative diseases; therefore, identifying novel compounds that can suppress adverse activation of glia is an important goal. We have previously identified a class of trisubstituted pyrazoles that possess neuroprotective and anti-inflammatory properties. Here, we describe a second generation of pyrazole analogs that were designed to improve their neuroprotective activity toward neurons under inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…A 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium Bromide (MTT) assay was performed as previously described [ 23 ] with slight modifications. On the day before treatment, NIH3T3 cells were seeded in a 96-well-plate (25,000 cells per well, Greiner, 655,180).…”
Section: Methodsmentioning
confidence: 99%
“…A 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium Bromide (MTT) assay was performed as previously described [ 23 ] with slight modifications. On the day before treatment, NIH3T3 cells were seeded in a 96-well-plate (25,000 cells per well, Greiner, 655,180).…”
Section: Methodsmentioning
confidence: 99%
“…This indicated that the LPS activated the migratory behavior of THP-1 and caused the decrease of SH-SY5Y cell activity due to production of cytotoxic factors, demonstrating consistency with previous results. 32,33 Additionally, because the THP-1 cells were treated by live cell staining in advance, the mobility of the THP-1 cells could be observed by measuring the absorbance (OD 500 nm ) of the staining pigment in the culture medium (Fig. 6A).…”
Section: Migration Of Monocytes After Neuroinflammatory Injurymentioning
confidence: 99%
“…In light of this review, promising cytotoxic activities of some analogs against breast cancer cell lines (MCF-7 and MDA-MB-231) is expected to stimulate extensive evaluation of their effects on lung cancer (A-549), liver cancer (HepG-2), and brain cancer (HeLa) cell lines (Lv et al, 2016;Lehmann et al, 2017;Turkan et al, 2018;McKenzie et al, 2019;Bennani et al, 2020;Masaret, 2021). As a life-threatening health issue and one of the most lethal diseases known, cancer can be managed by targeting gene expression, certain protein synthesis, functions of organelles, pH, and electrolytes (Johnston and Strobel, 2020).…”
Section: Final Considerations and Future Perspectivementioning
confidence: 99%
“…Chemically diverse pyrazole analogs have shown promising cellular or neuronal protections. The bulky dicyclohexylamide ( 9 ), smaller dimethylamide ( 10 ), and aminophenyl ( 11 ) (pyrazole analogs with sterically hindered substituents on amide) attenuated microglia-mediated neurotoxicity (IC 50 = 10–50 µM) better than compound 12 (IC 50 = 100 µM) with high susceptibility to electrophilic displacement ( McKenzie et al, 2019 ). This compound contains an allyl group on an electron-deficient amide.…”
Section: Selected Activitiesmentioning
confidence: 99%